Anti-diabetic effects of glucomanno-oligosaccharides via AMPK activation in C2C12 myotubes - Tran, Nu Thi; Que, Do Thi Nguyet; Nhi, Tran Thi Y; Thien, Do Truong (Vietnam Journal of Science and Technology, 2021)
Abstract-HCTN7. In this paper, antidiabetic activities of glucomanno-oligosaccharides (GMO) in vitro and in vivo were investigated. GMO significantly increased AMP-activated protein kinase (AMPK) phosphorylation in a concentration-independent manner. Treatment with 100μg/ml and 50μg/ml of GMO for 1 hour caused 1.47-fold and 1.81-fold phosphorylation of AMPK, respectively. Oral administration of GMO (6g/kg-1 of body weight day-1) lowered blood glucose levels (p < 0.05) at 120 min as compared to control group. These results suggested that GMO exhibited anti-diabetic effects via activation of AMPK and could be useful for diabetes prevention